2020
DOI: 10.1136/injuryprev-2019-043426
|View full text |Cite
|
Sign up to set email alerts
|

Plight of the distracted pedestrian: a research synthesis and meta-analysis of mobile phone use on crossing behaviour

Abstract: BackgroundPedestrians are commonly involved in vehicle collisions that result in injuries and fatalities. Pedestrian distraction has become an emerging safety issue as more pedestrians use their mobile phones while walking and crossing the street.ObjectivesThe purpose of this research synthesis and meta-analysis is to determine the extent to which cell phone conversation, text messaging or browsing, and listening to music affect a number of common pedestrian behavioural measures.MethodsA keyword search was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Since advances in smartphone technology have transformed this hand-held device into an everyday social and/or professional necessity, maintaining an upright posture or walking while talking or texting on the phone are frequently met dual-task demands. The safe use of a phone during daily activities, like standing, walking, stair gait, crossing streets and driving has been studied, since all these acts require cognitive and motor abilities, as well as the division of attention [13][14][15][16][17][18][19]. Texting proved to have a higher detrimental effect on balance, gait and walking behavior in comparison to talking on the phone, increasing the postural sway and decreasing the gait velocity, stride length and cadence [4,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Since advances in smartphone technology have transformed this hand-held device into an everyday social and/or professional necessity, maintaining an upright posture or walking while talking or texting on the phone are frequently met dual-task demands. The safe use of a phone during daily activities, like standing, walking, stair gait, crossing streets and driving has been studied, since all these acts require cognitive and motor abilities, as well as the division of attention [13][14][15][16][17][18][19]. Texting proved to have a higher detrimental effect on balance, gait and walking behavior in comparison to talking on the phone, increasing the postural sway and decreasing the gait velocity, stride length and cadence [4,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Scienti c social networks have been investigated in the following main thematic areas: informaticsdocuments (33.8%), informatics and librarianship -350 documents (28.8%), mechanical engineering and technology -105 documents (8.6%), science and technology -88 documents (7.2%), education -63 documents (5.2%). The presence in the sample of articles related to thematic sections of the medical direction is due to the fact that social scienti c networks (ResearchGate, Mendeley) are used by physicians and biologists to select literature for a review, systematic review, meta-analysis (Agrawal et al 2020;Bajwa et al 2017;Simmons et al 2020;Weldegebreal and Worku 2019). The analyzed array of 1216 documents includes about 140 publications containing terms (review and "systematic literature search" or "systematic review*" or meta-analysis) in the title, abstract or indexed terms, referred to the areas of Pharmacology Pharmacy Public, Surgery, Neurosciences Neurology, General internal medicine, Environmental Occupational Health, Medicine General Internal, Clinical Neurology, Dentistry Oral Surgery Medicine, etc., in the overwhelming majority of cases, medical, research areas.…”
Section: Learned Publishing 10mentioning
confidence: 99%
“…Most importantly, an increase in road fatalities hinders attainment of target 3.6 of the Sustainable Development Goals: reducing fatalities in road crashes by 50% by 2020 to ensure healthy lives and promote well-being for all at all ages [5] The literature suggests that pedestrians are the most vulnerable in traffic mishaps; however, intensity of loss of lives is lower in high-income countries [6]. There are several reasons responsible for pedestrian's fatalities in a road crash including the design of roadways and pedestrian infrastructure [7,8], speed of vehicles [9,10], influence of alcohol on drivers or pedestrians [11,12], volume of traffic [13,14], insufficient visibility of pedestrians [15,16], age of pedestrians [17,18], safety measures in and around public transit [19,20], land-use planning factors [21,22], and recent socio-technical changes such as emergence of autonomous vehicles [23] and relentless use of smartphones [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, Nasar and Troyer [27] reported that the injuries (mostly non-fatal) among pedestrians in USA has increased in recent years because of using smartphones while walking. In an important experimental study, Simmons et al [24] observed that using smartphones while crossing distracts pedestrians and reduces the rate of watching their left and right sides while crossing. Hence, the ubiquity of smartphones use is distracting both the drivers and pedestrians, which is endangering their health and life.…”
Section: Introductionmentioning
confidence: 99%